Pengaruh Penyiaran Berita Radio Terhadap Kepuasan Pendengar Pada Ganie Radio 93.3 Fm Simalungun - Winda Kustiawan; Dina Evi Rahmi; Muhammad Ghazali; Ajniver Hamnur Zebua; Nayla Aidilla Sambas (Peneliti.net, 2023)
This study aims to determine the effect of radio news broadcasting on listener satisfaction at Ganie Radio 93.3 FM Simalungun. This study uses a quantitative approach with survey research methods and uses a simple linear regression analysis method. Test the data using SPSS 23 for Windows. The author used 35 samples of listeners to Ganie Radio 93.3 FM Simalungun. The results showed that the analysis used was simple regression analysis Ŷ = 6.381 + 0.824x. Based on the results of the analysis, it can be drawn that the t test results obtained t count ((6.381) > t tallble (1.694) with a significant value of 0.000 <0.05 meaning that there is a significant influence of Radio News Broadcasting significantly affecting Listener Satisfaction at Ganie Radio 93.3 FM Simalungun.